Nutritional disorders in tropical tuber crops: Diagnosis and management - John, K Susan; Ramesh, V; Laxminarayana, K (Indian Horticulture, 2025)
Tropical tuber crops such as cassava, sweet potato, yams, taro, and elephant foot yam are commonly cultivated in acidic, nutrient-deficient soils, making them vulnerable to nutritional disorders. These disorders arise due to imbalances or deficiencies of essential nutrients, including primary (N, P, K), secondary (Ca, Mg, S), and micronutrients (Fe, Cu, Mn, Zn, B). Diagnosis is primarily through visual symptom observation, soil analysis, and plant tissue analysis. Each nutrient displays characteristic symptoms—such as chlorosis, necrosis, or distorted growth—depending on its mobility within the plant. Management includes soil amendments, foliar applications, and use of customized fertilizers based on crop specific nutrient requirements. Strategies like foliar sprays of urea, SOP, CaNO2, and micronutrients (Zn, B, Fe) are used to mitigate acute symptoms. Prophylactic measures, including lime or dolomite application in acidic soils, are also critical. Early detection and targeted nutrient management are essential for maintaining crop health and improving productivity in tropical tuber crops.